A conceptual framework for the analysis of the use of advanced communication technologies in higher education: the institutional perspective - Baptista, João
This paper presents and discusses a conceptual framework designed to analyze how higher education institutions are using advanced communication technologies to support learning. The focus is on the institutional perspective and the paper includes a review of literature and a proposal of a model of analysis, supported by two main concepts – institutional framework and use, whose dimensions and components are detailed. The application of this model to the Portuguese public higher education system is presented, and some major results are summarized. Some final remarks about the application of this conceptual framework to other higher education contexts are also included.